2021
DOI: 10.3389/fnmol.2021.556215
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Astrocytes and microRNA Dysregulation in Neurodegenerative Diseases: From Pathogenesis to Therapeutic Potential

Abstract: Astrocytes are the most widely distributed and abundant glial cells in the central nervous system (CNS). Neurodegenerative diseases (NDDs) are a class of diseases with a slow onset, progressive progression, and poor prognosis. Common clinical NDDs include Alzheimer’s disease (AD), Parkinson’s disease (PD), amyotrophic lateral sclerosis (ALS), and Huntington’s disease (HD). Although these diseases have different etiologies, they are all associated with neuronal loss and pathological dysfunction. Accumulating ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 124 publications
0
8
0
Order By: Relevance
“…Treatment for the targets of genes is the most efficient and accurate, and also provides the development of novel drugs. It has been proven that miRNAs have a relatively small molecular weight and they can readily pass the BBB and exhibit stable expression in peripheral blood ( Bai et al, 2021 ). Since the permeability of BBB will increase after stroke ( Abdullahi et al, 2018 ), the concentration of miRNAs in the blood may be used as an indicator that prompts stroke prognosis, and could also help predict the outcome of post-stroke rehabilitation ( Mirzaei et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Treatment for the targets of genes is the most efficient and accurate, and also provides the development of novel drugs. It has been proven that miRNAs have a relatively small molecular weight and they can readily pass the BBB and exhibit stable expression in peripheral blood ( Bai et al, 2021 ). Since the permeability of BBB will increase after stroke ( Abdullahi et al, 2018 ), the concentration of miRNAs in the blood may be used as an indicator that prompts stroke prognosis, and could also help predict the outcome of post-stroke rehabilitation ( Mirzaei et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs play an important role in cell differentiation, organ development, and cell fate determination, and are also involved in various human pathologies ( Ha and Kim, 2014 ). Emerging studies have shown that many miRNAs are expressed in astrocytes, and some are involved in astrocyte differentiation, activation, and reprogramming activities ( Bai et al, 2021 ). As miR-9 and miR-124 control multiple genes regulating neuronal differentiation and function, Yoo et al (2011) proposed that these miRNAs might contribute to neuronal fates.…”
Section: Astrocyte Reprogramming Through Trans-differentiationmentioning
confidence: 99%
“…Here, we review accumulating evidence implicating disrupted miRNA expression in astrocytes and ADEVs in the pathophysiology of neurodegenerative diseases, highlighting downstream targets of the perturbed miRNA and the biological pathways affected. We build on recent reviews ( Neal and Richardson, 2018 ; Bai et al, 2021 ) by considering alterations to astrocytic miRNA expression in ADEVs and that arising from ageing and inflammatory processes. It is important to note that studies utilising astrocytoma or glioblastoma cells to represent astrocytes were not included due to the well-documented differences in miRNA expression between primary astrocytes and cultures derived from astrocytoma cell lines ( Lee et al, 2013 ; Zhou et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%